2005
DOI: 10.1007/s00284-005-4491-z
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Species Diversity in Cigarettes Linked to an Investigation of Severe Pneumonitis in U.S. Military Personnel Deployed in Operation Iraqi Freedom

Abstract: This report presents results from a study on the bacterial diversity of cigarette brands collected from military personnel during the U.S. Army's investigation of a series of cases of acute eosinophilic pneumonitis in military personnel deployed in Operation Iraqi Freedom. Eight species of Bacillus, including five new species, and one new species of Kurthia were isolated from the cigarettes. Some of these species have been identified elsewhere as causes of hypersensitivity pneumonitis and other respiratory syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
1
31
0
1
Order By: Relevance
“…In addition, during the course of our studies we found that the strains formed distinct groups. The taxonomic identity of these unique groups was investigated by amplifying and sequencing a fragment of the 16S ribosomal RNA (rRNA) gene using the primers and PCR protocol in Rooney et al (2005). The sequencing reactions were performed as described above.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, during the course of our studies we found that the strains formed distinct groups. The taxonomic identity of these unique groups was investigated by amplifying and sequencing a fragment of the 16S ribosomal RNA (rRNA) gene using the primers and PCR protocol in Rooney et al (2005). The sequencing reactions were performed as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The 16S ribosomal RNA gene from all strains was amplified and sequenced using primers and protocols as described in Rooney et al (2005Rooney et al ( , 2009bRooney et al ( , 2011. Amplified products were purified using ExoSAP-IT (Affymetrix, Santa Clara, CA) and sequenced using BigDye 3.1 on an ABI model 3730 sequencer in the NCAUR core sequencing facility.…”
Section: Methodsmentioning
confidence: 99%
“…The growth of bacteria and mold from warehouse tobacco has been described in the scientific literature and US Patents [28,[33][34][35][36][37][38][39][40]. Candidate microbial agents that have been identified in tobacco are reasonably anticipated to activate lung Ma are very diverse [28,[33][34][35][36][37][38][39][40][41][42][43].…”
Section: Microbial Toxins In Tobacco and Tobacco Smokementioning
confidence: 99%
“…Candidate microbial agents that have been identified in tobacco are reasonably anticipated to activate lung Ma are very diverse [28,[33][34][35][36][37][38][39][40][41][42][43]. Examples of the tobacco-associated microbes that could activate human lung Ma include both Gram-negative and Gram-positive tobacco-derived bacteria.…”
Section: Microbial Toxins In Tobacco and Tobacco Smokementioning
confidence: 99%
See 1 more Smart Citation